Functional Annotation of Small Noncoding RNAs Target Genes Provides Evidence for a Deregulated Ubiquitin-Proteasome Pathway in Spinocerebellar Ataxia Type 1 - Persengiev, Stephan; Kondova, Ivanela; Bontrop, Ronald E. (Journal of Nucleic Acids, 2012)
Spinocerebellar ataxia type 1 (SCA1) is a neurodegenerative disorder caused by the expansion of CAG repeats in the ataxin 1 (ATXN1) gene. In affected cerebellar neurons of patients, mutant ATXN1 accumulates in ubiquitin-positive nuclear inclusions, indicating that protein misfolding is involved in SCA1 pathogenesis. In this study, we functionally annotated the target genes of the small noncoding RNAs (ncRNAs) that were selectively activated in the affected brain compartments. The primary targets of these RNAs, which exhibited a significant enrichment in the cerebellum and cortex of SCA1 patients, were members of the ubiquitin-proteasome system. Thus, we identified and functionally annotated a plausible regulatory pathway that may serve as a potential target to modulate the outcome of neurodegenerative diseases.